ANALISIS KONFLIK BATIN PADA TOKOH UTAMA DALAM FILM “RUROUNI KENSHIN” KARYA KEISHI OTOMO - Sekarani, Katya (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2025)
This study analyzes the internal conflict experienced by the character Himura Kenshin in the film Rurouni Kenshin: The Origins, directed by Keishi Otomo. The focus of this research is to examine the forms of conflict, the influencing factors, and the personality structure of the main character. To analyze the internal conflict, the study applies literary psychology. The analysis begins by using Sigmund Freud’s psychoanalytic theory (1979) to examine the id, ego, and superego, as well as the factors that influence Kenshin’s internal conflict. In addition, Kurt Lewin’s theory (1997) is used to analyze the forms of conflict. The results of the study indicate that Himura Kenshin’s personality structure functions in a relatively balanced manner. The forms of internal conflict he experiences in the film include approach-avoidance conflict and avoidance-avoidance conflict. These conflicts are influenced by personality-related factors.